Validation of the binding stoichiometry between HCN channels and their neuronal regulator TRIP8b by single molecule measurements - Saponaro, Andrea; Vallese, Francesca; Porro, Alessandro; Clarke, Oliver B. (Frontiers in Physiology, 2022)
Tetratricopeptide repeat–containing Rab8b-interacting (TRIP8b) protein is a brain-specific subunit of Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels, a class of voltage-gated channels modulated by cyclic nucleotides. While the interaction between TRIP8b and the cytosolic C terminus of the channel has been structurally described, the HCN:TRIP8b stoichiometry is less characterized. We employed single molecule mass photometry (MP) to image HCN4 particles purified in complex with TRIP8b. Our data show that four TRIP8b subunits are bound to the tetrameric HCN4 particle, confirming a 1:1 stoichiometry.